Inovasi Sistem Informasi Manajemen Pendidikan Berbasis Aplikasi Sistem Informasi Santri di Pondok Pesantren Darussalam Blokagung Banyuwangi - Muhammad Ma'sum (MANAGIERE: Journal of Islamic Educational Management, 2024)
In the development of the world of education, especially in Islamic boarding schools, information is also something that is taken into consideration. The information processed in education is in the form of an information system. The development of management information systems (SIM) in educational institutions is a necessity. It is urgent to be implemented in terms of regulatory requirements and the demands of community needs. In this case, Islamic boarding schools are challenged to respond to globalization critically and wisely. The focus of this research is: 1) What is the Management Information System (SIM) innovation process at the Darussalam Islamic Boarding School Blokagung Banyuwangi? 2) How is the Santri Information System (SIS) application used at the Darussalam Islamic Boarding School Blokagung Banyuwangi? 3) What are the supporting and inhibiting factors in implementing the Santri Information System (SIS) at the Darussalam Islamic Boarding School Blokagung Banyuwangi? This research is a qualitative descriptive study with a case study type. Data collection techniques use passive participant observation, in-depth interviews, and documentation. This research's data analysis technique uses descriptive data analysis with an interactive model. Data validity uses credibility, transferability, dependability and confirmability. This research is to understand the innovation process of educational management information systems and the use of the Santri Information System (SIS) application as well as the supporting and inhibiting factors in implementing the application. The results of this research are the management information system (SIM) innovation process at the Darussalam Blokagung Islamic boarding school to facilitate the services of santri guardians so that the Santri Information System application is created. To use the Santri Information System application, download the application in the Play Store, enter the application and log in using the student's identification number, date of birth and the application is ready to use according to the usefulness of the available features. Supporting factors are getting support from caregivers, santri guardians, alumni, and the banking sector as well as Human Resources, Information Technology (IT) which facilitates it, while inhibiting factors are the lack of knowledge among santri guardians about the operation of the Santri Information System application.